Stylized facts about the gender wage gap: Evidences from a region of Peru - et. al., Lindon Vela Meléndez , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An exploration of the theoretical approach to the gender wage gap from 1993 to 2020 was carried out by using bibliometrics. Then, based on the National Household Survey (ENAHO) of Peru - Lambayeque (2015 -2019), an analysis of the phenomenon of wage differences between men and women was made. The bibliometric analysis shows an important approach to the topic, as publications have been increasing and diversifying the areas of interest such as: social sciences, economics, business and medical sciences. Theoretical approaches to the subject are: neoclassical, heterodox institutional economics, the social provisioning approach and other important theoretical contributions are abstractions such as the Sticky floor effect and glass ceiling effect and discrimination theories. Stylized facts show that the monetary labor income obtained by workers, both on a monthly and hourly basis, is different according to the sex of the worker, resulting in the gender wage gap going from 42.7% in 2015 to 34.4% in 2019 in its monthly form and from 26.5% in 2015 to 18.6% in 2019 when hourly income is taken into account, in addition, the presence of the phenomenon called "sticky-floor" and "glass-ceiling" has been evidenced.